The potential of urinary miR-200c-3p as a biomarker of fluorosis in rats - Ailin Li; Jian Wang; Xinyue Meng; Xu Ma; Ying Liu; Hanying Li; Zhe Mo; Rui Zhang; Lei Wu; Shirui Yan; Paula Fiorella Chacon Campoverde; Gazala Zafar; et al. (Ecotoxicology and Environmental Safety)
Fluorine is a strong oxidizing element and excessive intake can have harmful effects, particularly on the body's calcified tissues. Recent studies have demonstrated a link between miRNA and fluorosis. This study aimed to evaluate the time-dose-effect relationship of miR-200c-3p in plasma, urine and cartilage of rats with drinking water fluorosis, and to explore its potential as a biomarker. Analyses were conducted using Generalised linear models, Restricted cubic spline, Spearman correlation analysis, and Receiver operating characteristic curve (ROC). Results indicated that both fluoride exposure time and dose had significantly affected on urinary and cartilage miR-200c-3p expression in rats, while plasma miR-200c-3p expression was only influenced by fluoride exposure time. Restricted cubic spline plots revealed that urinary miR-200c-3p was non-linearly and positively correlated with serum fluoride, urinary fluoride, dental fluorosis, and Mankin score groups, and also linearly and positively correlated with cartilage fluoride. Regression analysis showed that for each unit increase in urinary miR-200c-3p, the likelihood of dental fluorosis increased by 1.300 times, and in the Mankin score groups, the likelihood increased by 1.251 times. The ROC curves demonstrated that urinary miR-200c-3p had high sensitivity and specificity in diagnosing dental and skeletal fluorosis. Blood and cartilage miR-200c-3p showed weaker diagnostic efficacy. In summary, fluoride has different effects on the expression levels of miRNA-200c in various biological samples of rats, and miRNAs in urine demonstrate potential as biomarkers for fluorosis.